MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR - Feni Dini Riskia; Sumadi Sumadi; Sugeng Widodo (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out the improvement of the activity and achievement of students during cooperative learning model Number Heads Together type, whose standard competence was to understand the economic activities of society. This research was carried out at SMPN 1 Mesuji Ogan Komering Ilir subdistrict, South Sumatra in the even-year semester 2011/2012 to 30 of VII2 students. The researcher used Classroom Action Research (CAR) method which was done in 2 cycles. The activities were planning, implementation of the action, observation, and reflection for each cycle. To collect the data, the researcher used observation, field notes and tests at the end of each cycle. The results of this research showed the scores of students learning activities at the cycle I was 54,99%. In the cycle I, learning activities was done by group discussions and presentation with numbering. In the cycle II, there was an improvement 23,34% so it became 78,33%. The treatment of learning activity at this cycle was different. Besides, the students were given chance to do group debates in order for all students to participate at the presentation activities. While the average of students achievement in cycle I was 59,33, in cycle II it improved to 73,33. The average of students achievement who get the score ≥ 70 at the cycle I was 57%, at cycle II there was an improvement 29,66% so it became 86,66%. It can be concluded that cooperative learning model Number Heads Together type can be applied as an alternative learning to improve the activity and achievement of VII2 social class students at SMP Negeri 1 Mesuji. Keywords  : cooperative learning model NHT type, Geography Education, fkip,unila